Mid-Term Appraisal Eleventh Five Year Plan 2007-2012 - Planning Commission, Government of India (Planning Commission, Government of India, 2007)
The Eleventh Plan (2007-08 to 2011-12) sought to build on the gains achieved in the Tenth Plan and shift the economy to a path of faster and more inclusive growth. Inclusiveness, a critical element in the strategy, was to be achieved by ensuring that growth was broad-based and was combined with programmes aimed at overcoming deficiencies in critical areas, which affect large numbers of the vulnerable sections of our population, particularly the Scheduled Castes (SCs), Scheduled Tribes (STs), the Other Backward Classes (OBCs), women, and the minorities.
Planning Commission Government of India
Planning Commission Government of India
Keywords: Eleventh Five Year Plan- India; Economic development in India